Literasi Lingkungan Masyarakat Adat dan Masyarakat Perkotaan di Pulau Lombok - Bidarinjani, Mouria; Rahardjanto, Abdulkadir; Setyawan, Dwi (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: The high ability of community environmental literacy can form ideal environmental conditions, but indigenous peoples and urban communities have different understandings of environmental conditions. This study aimed to determine differences in the environmental literacy of indigenous peoples and urban communities on Lombok Island. Methods: The objects of this research are the indigenous people of Bayan Village, North Lombok, and the people of the Dasan Sari Environment, Mataram City, West Lombok: quantitative research methods, quantitative descriptive approaches, and survey research types. Data collection tools are observation, interviews, and questionnaires. Data analysis using SPSS, data analysis techniques by calculating the mean score of the questionnaire. Results: The study obtained a mean environmental literacy value for the indigenous people of Bayan Village at 214.37 and for the Dasan Sari Environmental community at 240.56. The results of the hypothesis testing in this study obtained a significance value greater than 0.05 and t-count < t-table. Conclusions: There was no real difference in environmental literacy between indigenous peoples and urban communities on Lombok Island.